2018
DOI: 10.1111/tra.12545
|View full text |Cite
|
Sign up to set email alerts
|

Ergosterol is mainly located in the cytoplasmic leaflet of the yeast plasma membrane

Abstract: Transbilayer lipid asymmetry is a fundamental characteristic of the eukaryotic cell plasma membrane (PM). While PM phospholipid asymmetry is well documented, the transbilayer distribution of PM sterols such as mammalian cholesterol and yeast ergosterol is not reliably known. We now report that sterols are asymmetrically distributed across the yeast PM, with the majority (~80%) located in the cytoplasmic leaflet. By exploiting the sterol-auxotrophic hem1Δ yeast strain we obtained cells in which endogenous ergos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 79 publications
10
91
0
Order By: Relevance
“…In a recent study, the natural ergosterol in an auxotroph of Saccharomyces cerevisiae was completely replaced by dehydroergosterol (DHE), enabling the surface accessibility of the sterol to be determined with impermeant fluorescence quenchers, as described above. 75 An exhaustive study suggested that~70% of cellular DHE was located in the plasma membrane and~80% of that resided the inner leaflet thereof, in agreement with the aforementioned studies using the DHE quenching approach. This analysis took into account both the incomplete quenching of accessible DHE and the (inaccessible) intracellular pool which would otherwise be scored with the cytoplasmic leaflet.…”
Section: Dhe Quenching In Yeastsupporting
confidence: 80%
See 3 more Smart Citations
“…In a recent study, the natural ergosterol in an auxotroph of Saccharomyces cerevisiae was completely replaced by dehydroergosterol (DHE), enabling the surface accessibility of the sterol to be determined with impermeant fluorescence quenchers, as described above. 75 An exhaustive study suggested that~70% of cellular DHE was located in the plasma membrane and~80% of that resided the inner leaflet thereof, in agreement with the aforementioned studies using the DHE quenching approach. This analysis took into account both the incomplete quenching of accessible DHE and the (inaccessible) intracellular pool which would otherwise be scored with the cytoplasmic leaflet.…”
Section: Dhe Quenching In Yeastsupporting
confidence: 80%
“…However, this appears not to be the case for intact yeast cells (Müller et al, personal communication). Also, 4‐SLPC gave results comparable to TNBS, seeming to validate its use . Like cholesterol itself, DHE can move rapidly between the plasma membrane and intracellular compartments .…”
Section: Evidence For Excess Cholesterol In the Inner Leafletmentioning
confidence: 71%
See 2 more Smart Citations
“…In budding yeast, Bem1 is proposed to play a role in this feedback (Bose et al, 2001;Goryachev & Pokhilko, 2008;Witte et al, 2017); however, the mechanisms that localize Bem1 to the plasma membrane to trigger the positive feedback have been enigmatic. Interestingly, ergosterol levels have been reported to be non-homogeneous in the yeast plasma membrane, where it was observed to cluster, although another study reported a more homogeneous distribution (Grossmann et al, 2007;Solanko et al, 2018). Moreover, our solid-state NMR spectroscopy experiments suggest that the interaction between Bem1 and anionic lipids is reciprocal in the sense that Bem1 influences the ordering of lipid acyl chains, rigidifying the local membrane environment where ergosterol levels are low, while fluidizing it where ergosterol levels are high.…”
Section: Discussionmentioning
confidence: 60%